Penerapan Konsep Rekreasi Pada Pusat Wisata Edukasi Kain Endek Di Kabupaten Klungkung: bahasa indonesia - I Gede Yusa Prayoga; I Nyoman Gede Maha Putra; I Putu Hartawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
In Bali, weaving is a traditional craft that has been practiced for a long time. Weaving is now more than just a side job or a way to fill time, but has also developed into a creative industry. The process of interweaving the warp and weft threads is known as weaving. The weft thread attached to the warp thread and attached to the loom, and the warp thread which, when connected, will produce a motif. In this study, three research methods were used: Literature Study, in a method for systematically analyzing data using summarized versions of the data, such as books, journals, or articles, in the classroom. Direct interviews with related parties in the Balinese endek woven fabric industry were used as a data collection method. Precedent studies, surveying observers regarding architectural approaches to planning and designing educational tourism centers for woven fabrics in Klungkung district and indirectly searching for other objects outside Bali via the internet are the methods used to collect data. In the Planning and Design of the Endek Cloth Educational Tourism Center in Klungkung Regency, Bali has the overarching objectives of helping tourism development and providing new innovations in the field of endek woven cloth centers, and being able to provide learning about endek cloth processing. Endek cloth educational tourism centers in the district Klungkung can have a positive impact on the community in the surrounding Klungkung district and help develop tourism.